Immunomodulatory effect of ibrutinib: Reducing the barrier against fungal infections. (March 2020) - Maffei, Rossana; Maccaferri, Monica; Arletti, Laura; Fiorcari, Stefania; Benatti, Stefania; Potenza, Leonardo; Luppi, Mario; Marasca, Roberto
Abstract: The Bruton tyrosine kinase (BTK) inhibitor ibrutinib is increasingly used in the treatment of chronic lymphocytic leukemia (CLL). Moreover, very promising results have been reported in other B-cell malignancies, including primary central nervous system lymphoma (PCNSL). Although well-tolerated in the majority of patients, ibrutinib demonstrates in some cases troublesome toxicities, including invasive fungal infections (IFIs). In the present review, we summarize clinical manifestations of IFIs in patients treated with ibrutinib, generally characterized by an early onset, mild clinical manifestations, asymptomatic/low symptomatic pulmonary localization and high incidence of central nervous system (CNS) involvement. IFI risk appears particularly increased in patients receiving ibrutinib associated with other immune modulator agents, especially with steroids or immune-chemotherapy. Moreover, the immunomodulatory effect of ibrutinib is described, pointing the attention on the involvement of specific molecules targeted by ibrutinib in innate and adaptive response to fungal infection. Overall, the findings indicate the ibrutinib may rapidly impair innate immune cell functions, while concomitantly restoring an effective protective potential of adaptive immune compartment. A correct awareness, especially when other predisposing factors are present, is warranted about the potential risk of IFIs in ibrutinib-treated patients.